2021
DOI: 10.3390/agriculture11040290
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Poultry Manure and Biochar on Acrisol Soil Properties and Yield of Common Bean. A Short-Term Field Experiment

Abstract: Common bean is usually cropped under rainfed conditions and in soils with low pH and water retention, in the sub-humid and semiarid regions of Brazil. To improve soil conditions, smallholder farmers commonly use cattle manure. However, manure is available in limited amounts, insufficient to fertilize all cropping areas. Thus, other amendments, such as poultry manure (PM) and biochar (BC), have been proposed to increase soil water retention and pH. We evaluated the effects of BC (10, 20, and 40 t ha−1; BC10, BC… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 23 publications
(10 citation statements)
references
References 57 publications
0
10
0
Order By: Relevance
“…Recent studies have focused on the benefits arising from the enrichment or coapplication of manure with biochar or humic substances [8,9]. Biochar is a charred organic material used to enhance soil fertility and to sequester carbon [10].…”
Section: Introductionmentioning
confidence: 99%
“…Recent studies have focused on the benefits arising from the enrichment or coapplication of manure with biochar or humic substances [8,9]. Biochar is a charred organic material used to enhance soil fertility and to sequester carbon [10].…”
Section: Introductionmentioning
confidence: 99%
“…Interestingly, the results showed that the higher rate of chicken manure application improved the soil chemical properties by increasing the organic matter, total N, available P, and available K at all three harvest times, these effects were not found in the chemical fertilizer soil. Chicken manure can slowly supply the plant nutrients and also has a high organic matter content (559.30 g kg -1 ) which can improve soil’s physical properties as reported by Lima et al [ 17 ]. The soil applied with both fertilizers had available P between 122 to 274 mg kg -1 and available K between 48 to 228 mg kg -1 .…”
Section: Resultsmentioning
confidence: 99%
“…Poultry manure was also reported to release nitrogen slowly, which resulted in significantly lower nitrate accumulation in plants [ 16 ]. Organic fertilizers, such as poultry manure, have been found to improve soils physical, chemical, and biological properties, including bulk density [ 17 ], organic carbon [ 18 ], and microbial biomass [ 19 ]. However, at present, there has not been any report about the effect of different dosages of chicken manure and chemical fertilizer on the yield and quality of white mugwort.…”
Section: Introductionmentioning
confidence: 99%
“…An increasing number of publications around the world have reported the effect of biochar amendments on all kind of soils under different climates (Adekiya et al, 2019; Al‐Wabel et al, 2018; Farhangi‐Abriz et al, 2021; Kavitha et al, 2018; Lima et al, 2018, 2021). Initially inspired by the Amazonian dark soils, ‘Terra Preta do Indio’, it is advocated to restore the fertility of tropical soils and especially in acidic sandy soils (Glaser & Birk, 2012; Lehmann et al, 2006; Lima et al, 2018; Silva et al, 2021).…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, in the context of climate change with forecast increases in extreme rainfall events and longer dry periods, it is essential to hold water and nutrients in order to conserve or increase soil fertility. To preserve and maximize the efficiency of scarce water and nutrient resources of these marginal lands, the use of biochar can be a promising sustainable solution (de Melo Carvalho et al, 2014;Dharmakeerthi et al, 2010;Lima et al, 2018Lima et al, , 2021Medeiros et al, 2020;Silva et al, 2021).…”
Section: Introductionmentioning
confidence: 99%